Experimental and Theoretical Investigation of the Polymer Optical Fiber Random Laser with Resonant Feedback. Issue 7 (7th February 2018) - He, Jijun; Chan, Wing‐KinEdward; Cheng, Xin; Tse, Ming‐LeungVincent; Lu, Chao; Wai, Ping‐KongAlexander; Savovic, Svetislav; Tam, Hwa‐Yaw
Abstract: 1D random fiber laser is a novel fiber‐based laser, which exhibits many unique optical properties and shows great promise for various applications including speckle‐free imaging. A multimode and coherent polymer optical fiber random laser (POFRL) is successfully fabricated by doping TiO2 nanoparticles and Rh640 perchlorate dyes in the core of a polymer optical fiber (POF). The waveguide effect provided by the POF greatly increases the multiscattering events for light propagation and results in laser cavity with much shorter length than the scattering mean free path. As an illustration of potential applications, a clear speckle‐free imaging is demonstrated using the POFRL as the illumination source. Furthermore, a four‐level Monte Carlo method‐based numerical model is proposed to describe the lasing dynamics in POFRL. The model supports the experimental work in the research field of POFRL. Abstract : Here, the random lasing properties of the particle‐doped polymer optical fiber random laser (POFRL) are experimentally and theoretically investigated. This POFRL shows coherent and multimode lasing behavior because of the multiscattering and reflection events provided by the doped particles and waveguide configuration. The corresponding random lasing dynamics are also realized in a modified Monte Carlo numerical model.